The Influence of Food Crop, Livestock, and Fishery Sub-Sectors on Gross Regional Domestic Product (GRDP) of Malang Regency - Junita Mega Sari Sihombing; Thomas Soseco (Politeknik Baubau, 2026)
The agricultural sector is an important sector in supporting the increase of Gross Regional Domestic Product (GRDP), especially the food crops, livestock, and fisheries sub-sectors in Malang Regency. This study aims to identify the contribution of the food crops, livestock, and fisheries sub-sectors in Malang Regency to GRDP in Malang Regency. The research method used is descriptive quantitative with secondary data obtained from the Central Statistics Agency of Malang Regency. The results of the study show that the independent variables of food crops, livestock, and fisheries simultaneously have a significant effect on the dependent variable GRDP. The partial test results show that the food crops and livestock sub-sector variables have a positive and significant effect on the dependent variable. The fisheries variable has a positive and insignificant effect on the dependent variable. The results of the determination coefficient test of 0.878 indicate that 87.8% of the variation in GRDP can be explained by the food crops, livestock, and fisheries sub-sectors, while the rest is influenced by other factors. From the research that has been done, the researcher suggests that the government should optimise the production of food crops, livestock, and fisheries production, because these three sub-sectors are potential sub-sectors in the agricultural sector in Malang Regency.